The use of bacteriophages as a solution for antibiotic resistance and its applications in industry: a literature review (Research, Society and Development, 2022)
Bacteria are microorganisms that cause relevant implications in humans, and there have been several attempts, over time, to promote their control. The most common and widespread form of control has been antibiotic drugs, which have been increasingly less effective, considering the mechanisms of adaptation and bacterial resistance, generating super-resistant bacteria. bacterial control. Among them, one that is especially relevant is the use of bacteriophages, viruses that infect specific bacteria, promoting cell lysis of these microorganisms. The objective of this study, therefore, is to analyze the application of the use of bacteriophages as a form of bacterial biocontrol, with emphasis on the applications of this form of control in the industry. Eleven articles from an initial sample of 3,460 were analyzed, which made it possible to evidence the applicability of the use of bacterial phages in agro-industry, in the food industry and in human health.